Management of chest pain: a prospective study from Norwegian out-of-hours primary care - Burman, Robert Anders (BioMed Central, 2014)
BACKGROUND: Chest pain is a common diagnostic challenge in primary care and diagnostic measures are often aimed at confirming or ruling out acute ischaemic heart disease. The aim of this study was to investigate management of patients with chest pain out-of-hours, including the use of ECG and laboratory tests, assessment of severity of illness, and the physicians’ decisions on treatment and admittance to hospital. METHODS: Data were registered prospectively from four Norwegian casualty clinics. Data from structured telephone interviews with 100 physicians shortly after a consultation with a patient presenting at the casualty clinic with “chest pain” were analysed. RESULTS: A total of 832 patients with chest pain were registered. The first 100 patients (corresponding doctor-patient pairs) were included in the study according to the predefined inclusion criteria. Median age of included patients was 46 years, men constituted 58%. An ECG was taken in 92 of the patients. Of the 24 patients categorised to acute level of response, 15 had a NACA-score indicating a potentially or definitely life-threatening medical situation. 50 of the patients were admitted to a hospital for further management, of which 43 were thought to have ischaemic heart disease. Musculoskeletal pain was the second most common cause of pain (n = 22). Otherwise the patients were thought to have a variety of conditions, most of them managed at a primary care level. CONCLUSIONS: Patients with chest pain presenting at out-of-hours services in Norway are investigated for acute heart disease, but less than half are admitted to hospital for probable acute coronary syndrome, and only a minority is given emergency treatment for acute coronary syndrome. A wide variety of other diagnoses are suggested by the doctors for patients presenting with chest pain. Deciding the appropriate level of response for such patients is a difficult task, and both over- and under-triage probably occur in out-of-hours primary care.